Improving Elementary School Students’ Learning Outcomes through Cooperative Learning Models in Islamic Religious Education - Arnilawati Arnilawati; Khermarinah Khermarinah (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: Learning outcomes in Islamic Religious Education at the elementary school level are strongly influenced by the learning models applied by teachers. Teacher-centered instructional practices tend to limit student participation and understanding, thus requiring the use of more interactive learning models, such as cooperative learning. Objective: This study aims to analyze the implementation of cooperative learning models and their effectiveness in improving the learning outcomes of fourth-grade elementary school students in Islamic Religious Education. Method: This research employed a quantitative approach. Data were collected through classroom observations and learning outcome tests. Data analysis was conducted using simple statistical techniques, including calculating mean scores, learning completeness, and learning achievement levels. Results: The findings indicate that applying the cooperative learning model improved students’ learning outcomes. This improvement is reflected in higher average test scores and greater learning completeness among students. Conclusion: The study concludes that cooperative learning models are effective in enhancing students’ learning outcomes in Islamic Religious Education at the elementary school level. Contribution: This research provides empirical evidence supporting the effectiveness of cooperative learning as an instructional strategy and offers practical insights for teachers to improve the quality of Islamic Religious Education instruction in elementary schools.